Respuesta :

(2p + 7)(3p^2 + 4p - 3) = 2p(3p^2 + 4p - 3) + 7(3p^2 + 4p - 3) =
6p^3 + 8p^2 - 6p + 21p^2 + 28p - 21 =
6p^3 + 29p^2 + 22p - 21 <===

Answer:

[tex]6p^{3} +29p^{2} +22p-21[/tex]

Step-by-step explanation:

This is a polynomial product where we have to apply distributive property and exponent properties (image is attached).

So, applying distributive property:

[tex](2p + 7)(3p^{2}  + 4p-3)\\6p^{3}+8p^{2}-6p+21p^{2}+28p-21[/tex]

Then, we reduce like terms:

[tex]6p^{3} +29p^{2} +22p-21[/tex]

Therefore, the product is

[tex]6p^{3} +29p^{2} +22p-21[/tex]

Ver imagen jajumonac
ACCESS MORE